Comparing radiation doses in CBCT and Medical CT imaging for dental applications - Mahmud U Zaman (Wolters Kluwer Medknow Publications, 2024)
Background: We are always concerned about radiation exposure during dental imaging procedures. We explore the crucial differences in radiation doses between Cone Beam Computed Tomography (CBCT) and Medical computed tomography (CT) imaging, aiming to shed light on the safety and efficiency of these techniques. Materials and Methods: In this study, we conducted a comprehensive analysis using state-of-the-art dental imaging equipment. We employed phantoms that simulated real dental scenarios, ensuring accuracy in our measurements. The radiation doses were measured with precision dosimeters, and various exposure settings were tested to obtain a comprehensive dataset. Results: Our findings reveal substantial differences in radiation doses between CBCT and Medical CT for dental applications. In the case of CBCT, the average effective dose was found to be approximately 100 microsieverts (μSv), making it a preferable choice for routine dental imaging. Medical CT, on the other hand, yielded significantly higher radiation exposure, with an average effective dose exceeding 500 μSv, emphasizing its need for specific clinical scenarios. Conclusion: In conclusion, the choice between CBCT and Medical CT for dental applications should be made with careful consideration of radiation dose implications. CBCT emerges as the safer and more efficient option for routine dental imaging, offering a lower radiation burden to patients while still delivering high-quality diagnostic images. However, Medical CT may be necessary for specialized cases where the additional radiation risk is justified by diagnostic requirements.